COMPREHENSIVE DECISION ANALYSIS: INFORMATION SYSTEM BASED ON CLASSICAL CRITERIA - Rozum, M. V.; Ihnatieva, K. M. (Systems and Technologies, 2026)
The study presents the development and implementation of a comprehensive information system for decision-making support based on classical criteria applied under uncertainty – Laplace, Wald, Savage, and Hurwicz. The system is designed as a tool for automating calculations, visualizing results, storing problem parameters, and ensuring increased accuracy in the analysis of alter- natives. This makes it effective for use both in the educational process, where it serves to demonstrate theoretical principles, and in applied analytical scenarios where rapid risk assessment, strategy comparison, and justification of an optimal choice are required. The system’s interface adaptation includes the introduction of a modern design, interactive graphical components based on Plotly, an optimized navigation structure, as well as support for data import and export in Excel format. This ensures conven- ience when working with large volumes of information and allows the user to quickly adjust problem parameters. The updated database structure includes new entities for storing the calculation history, problem parameters, and criterion types. This approach increases the system’s flexibility and scalability, creating the foundation for further functional expansion, integration of new methods, and development of additional modules. Each criterion is implemented as an autonomous software module with clearly structured data-processing logic. The user enters a payoff or loss matrix, after which the system automatically performs the calculations, generates intermediate coeffi- cients, and presents the final solution in a form convenient for analysis. Mechanisms for reusing parameters, generating reports, and storing all performed operations for subsequent analysis or comparison are provided.The presented implementation combines mathematical rigor with modern technological solutions, offering a compre- hensive tool for educational, research, and managerial applications. The system improves the quality of analytics, minimizes the influence of human error, and supports the adoption of strategically justified decisions across various domains.